SISTEM INFORMASI AKUNTASI (SAKTIPOL) UNTUK PENGELOLAAN KEUANGAN PRODUK BATIK DAN BORDIR DI DESA PAKISAJI KABUPATEN MALANG - Mungki Astiningrum; Yuri Ariyanto; Dwi Puspitasari; Atiqah Nurul Asri; Moch Zawaruddin A (Publisher UPT P2M Politeknik Negeri Malang, 2020)
The increasingly heavier life demands, especially in the economic sector, have encouraged housewives in Desa Pakisaji, Kabupaten Malang to set up Ron Tuwuh batik tulis business group and Prohandji Embroidery business group. The batik works are quite good and have begun to be well-known, especially among government agencies in Kabupaten Malang, as well as their embroidery works. There have been several steps taken to develop themselves in terms of design, namely by establishing a partnership with the 2019 Partnership PKM team of Information Technology Department of State Polytechnic of Malang. They have learned to design using applications built and as a result their designs become more up-to-date and the workmanship becomes more efficient. In an effort to sustain this program, this year the same team also continued PKM Partnership by solving other problems faced. From the results of interviews and observations conducted, it was found that each group had problems in the field of financial recording. The income of the batik cloth and the embroidered cloth are still recorded manually so that the financial recording process of both income and expenditure is ineffective and inefficient. From these problems, an Accounting Information System, SAKTIPOL was created which aims to assist both groups in the field of financial management. In addition, after the system was designed, this team then provided training and assistance in the use of this computer and internet-based application.